Mesoscale Eddies Observed at the Denmark Strait Sill - Moritz, Martin; Jochumsen, Kerstin; North, Ryan P.; Quadfasel, Detlef; Valdimarsson, Héðinn (FID GEO, 2019)
The Denmark Strait overflow is the major export route of dense water from the Arctic Mediterranean into the North Atlantic. At the Strait's shallow sill, the overflow is a bottom-intensified cold and dense plume, bound to the east by a thermal front formed with the warmer, northward flowing North Icelandic Irminger Current. More than two decades of observations at the sill show strong fluctuations of volume flux on daily time scales. To better understand the source of this variability, a five-mooring array was installed at the sill, capturing nearly 1 year of velocity and bottom temperature measurements at a high temporal and spatial resolution. Bottom temperature fluctuations that exceed 4 °C indicate a meandering of the front between the plume and the North Icelandic Irminger Current. Current vector rotation shows trains of alternating cyclones and anticyclones at the sill. An eddy crosses the sill every 3 to 6 days with a mean velocity of 0.4 m/s and a typical diameter of 30 to 40 km. The results suggest that anticyclones, with centers passing through the deepest part of the sill, may be responsible for periods of increased volume flux—also referred to as boluses and pulses in previous studies. Although the relationship between eddies, pulses, and boluses is still unclear, the results show that eddies are directly linked to fluctuations in the strength, thickness, and position of the overflow plume.